Effects of Adult Attachment and Emotional Distractors on Brain Mechanisms of Cognitive Control. - Warren, Stacie L.; Bost, Kelly K.; Roisman, Glenn I.; Silton, Rebecca Levin; Spielberg, Jeffrey M.; Engels, Anna S.; Choi, Eunsil; Sutton, Bradley P.; Miller, Gregory A.; Heller, Wendy (Psychological Science., 2010)
A study examined effects of adult attachment on neural circuitry associated with top-down cognitive control in the presence of emotional distracters. Data were obtained from 34 participants who completed an emotion-word Stroop task while brain imaging was conducted. Findings indicated that participants with lower levels of secure-base-script knowledge reflected an adult's failure to generate narratives in which attachment-related threats are identified. Findings suggested that poor performance and related increased brain activity imply that insecure attachment involves susceptibility to distraction by attachment-relevant emotional information. Findings are discussed in detail.